Husband's intention to support during pregnancy for the use of maternity waiting home in Jimma Zone, Southwest, Ethiopia: a community-based cross-sectional study - Aman, Mamusha; Bekele, Adisu; Abamecha, Fira; Lemu, Yohannes Kebede; Gizaw, Abraham Tamirat (Frontiers in Global Women's Health, 2024)
Background: Husbands are the primary decision-makers about the place of childbirth. Lack of husbands' support for maternal health care is associated with low maternal waiting home utilization and less is known about the husbands' intention to support their wife's use of maternal waiting homes (MWHs) and underlying beliefs in Ethiopia. This community-based cross-sectional survey aimed to study husbands' intention to support during pregnancy through the use of maternity waiting homes in Jimma Zone, Southwest Ethiopia. Method: A cross-sectional study was conducted among 396 randomly selected husbands whose wives were pregnant. Interviewer-administered, a structured questionnaire developed based on the Theory of Planned Behavior (TPB) was used to collect the data. Multivariable logistic regression analyses were used to examine the association between behavioral intention and constructs of the theory of planned behavior. Results: Of the 396 husbands who took part in the study, 42.7% intend to support their partner's use of a maternity waiting home. Intention to support a wife to use a maternity waiting home was associated with subjective norm [AOR = 1.303, 95% CI (1.054, 1.611)] and perceived behavioral control [AOR = 1.446, 95% CI (1.234, 1.695)]. Among the control beliefs, "having childcare''; "having a person who stays with a wife at a maternity waiting home"; and "availability of quality service provided to a wife in the maternity waiting home" significantly separated intenders and non-intenders. Conclusion: The findings suggest that husbands who perceived more social pressure and felt in control of barriers were more likely to intend to support their partner in using a maternity waiting home. Intervention should focus on underlying normative and control beliefs to improve the husband's intention.